Estudo da influência do sistema de revestimento no desempenho térmico, acústico e lumínico de edifícios. - Gois, Pedro de Freitas (2020)
Regardless of the construction processes or employed materials, the NBR 15575 defines objectives, requirements, and methods for assessing the behavior in use performance of accommodations. Therefore, the influence of the coating layers on the performance of construction systems is an essential parameter to assess the use of materials and elements of the systems, in order, to make the project feasible, not only economically, but also technically. Through computer simulations based on a defined reference model for the study, the present work study the influence of different layers of floor, roof and, internal and external, vertical sealing systems, on the thermal, acoustic, and lighting performance. Finally, analyzing the results, for the reference model used, identified the materials and elements with the greatest influence on: lighting performance - the internal finishes of the environment and the type of glass used in the external frame; thermal performance - all elements of tension, roofing system and facades, especially an absence of external cladding and the roof system typology; acoustic performance of the façade - function especially of the external frame; acoustic performance of the floor system - mainly influenced by the thickness of the structural element and the use of ceiling and acoustic blanket; acoustic performance of internal vertical seals - typology of the structured element of the seal and thickness of the lining. We conclude that coatings have a great influence on the thermal, acoustic and natural lighting performance of buildings and should be considered in the design stage, with computer simulations as an important tool.